2006
DOI: 10.1111/j.1444-2906.2006.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding characteristics of the Zn-binding membrane protein from common carp

Abstract: This study incorporated the 43 kDa Zn-binding membrane protein isolated from common carp into liposome. The specificity and strength of the binding of 65 Zn to the 43 kDa proteinliposomes, and the binding of the 65 Zn-labeled 43 kDa protein-liposomes to laminin were studied. It was found that 65 Zn was bound to the external side of the 43 kDa protein-liposomes. Specific binding of 65 Zn to the protein-liposomes was detected. The binding parameter of Zn to the protein was found to be: maximum binding site (N ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It is very possible that when there is more Zn‐binding protein in the fibroblast, the more the collagen and glycosaminoglycans are secreted by the fibroblast. Recently, the authors incorporated the 43 kDa Zn‐binding protein isolated from common carp into liposome, studied its binding characteristics, and found that 65 Zn was bound to the external side of the 43 kDa protein‐liposomes, through SH groups with a Kd of 0.19 µM 17 In the common carp Zn might be bound to the external side of the fibroblast. Binding between the cell and extracellular matrix might be specifically mediated by laminin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very possible that when there is more Zn‐binding protein in the fibroblast, the more the collagen and glycosaminoglycans are secreted by the fibroblast. Recently, the authors incorporated the 43 kDa Zn‐binding protein isolated from common carp into liposome, studied its binding characteristics, and found that 65 Zn was bound to the external side of the 43 kDa protein‐liposomes, through SH groups with a Kd of 0.19 µM 17 In the common carp Zn might be bound to the external side of the fibroblast. Binding between the cell and extracellular matrix might be specifically mediated by laminin.…”
Section: Discussionmentioning
confidence: 99%
“…In the digestive tract of common carp, it seems that the high concentration of Zn comes from the first explanation. Because the 43 kDa Zn‐binding protein is a strong Zn binding agent (Kd = 0.19 µM) and the maximum binding site is approximately 3 mol Zn 2+ per mole, 17 when the Zn leaves intestinal cells, enters the extracellular matrix, it might be bound by the 43 kDa Zn‐binding protein present in the fibroblasts. Before the Zn can enter the blood, most is likely to be adsorbed by the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its Zn-chelating activity, OP has been employed as a probe to determine the importance of Zn as a functional component of metalloproteins (Woods and Roth 1984;Wang and Jeng 2006). Identification of the 30-and 35-kDa polypeptides as homologs of the Lv1 domain of zfVg1 correlated well with the metal-dependent, UV-damaged-DNA binding activities of the two molecules (Lai et al 2006).…”
Section: Discussionmentioning
confidence: 93%
“…The main body of high Zn in animal erythrocyte plasma membranes is not clear, the precise location of Zn in plasma membranes is also unknown 16 . Recently, Jeng and Wang incorporated the 43 kDa Zn‐binding protein isolated from common carp into liposome, and studied its binding characteristics 17 . By treating the protein‐liposome with 1, 10‐phenanthroline, it was found that 65 Zn was bound to the external side of the 43 kDa protein‐liposomes.…”
Section: Discussionmentioning
confidence: 99%